Impact of relative and absolute financial risks on share prices: a Zimbabwe Stock Exchange perspective - Atanas Sixpence; Olufemi P. Adeyeye; Rajendra Rajaram (Investment Management & Financial Innovations, 2020)
The impact of financial risks on share prices concerns investors, company executives and accounting standards developers. Investors need this information in delineating their equity valuation models while company executives need the information to make appropriate capital structure decisions. Accounting standards developers use this information in their policy to make accounting standards contemporary. The authors examine the link between relative and absolute financial risks and share prices using a dynamic panel of non-financial listed companies on the Zimbabwe Stock Exchange after dollarization. Equity investors incurred losses before dollarization, which prompted this investigation into the sphere of financial risks in order to explain share price movements so that investors can use it to minimize losses in the future. Absolute financial risk is measured by the total debt, while debt/equity ratio measures relative financial risk. Market capitalization as a proxy for equity and debt is measured by total liabilities. An average debt/equity ratio greater or equal to one qualifies a firm into the high-risk category while ratios below one imply low-risk firms. Results from two-step System Generalised Method of Moments (GMM) show negative and significant connection between relative risk and share prices across risk categories. The impact of absolute risk on share prices differs by risk category. Firm managers are advised to keep total liabilities below market capitalization in order to enjoy the benefits of low-risk categorization. Debt ratio is a reasonable indicator of value and investors can use it in equity valuation. Mandatory reporting of debt ratios should be considered by accounting standards developers.